Pembuatan Briket Pelepah Sawit Menggunakan Proses Torefaksi Pada Variasi Tekanan Dan Penambahan Perekat Tapioka - Pratama, Yudistira; Helwani, Zuchra; Komalasari, Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Palm frond so far only used as a source of raw materials for animal feed, compost and organic fertilizer in the plantation. Palm frond has a calorific value of 15184.05 kJ/kg with a density of 0.1383 g/cm3. The calorific value can be increased by densification. Dencification is one method to increase the density of the biomass so that it will increase the calorific value of the biomass. The purpose of this research is to produce solid fuel products from palm fronds uses densification process, to determine the characteristics of the product and determine the effect of tapioca adhesive composition and pressure in the process of densification in density, calorific value and proximate. Tapioca adhesive composition used were10, 20, 30 %. Pressure used were50, 75 and 100 bar. The particle size used were < 20 Mesh . The highest density and calorific value of the product is 1.1375gr/cm3and 5144,94cal/gr was obtained at tapioca adhesive composition 30% and pressure 100 bar.Keywords :Densification, Density, Tapioca Adhesive, Pressure, Palm Fronds.